2013
DOI: 10.3922/j.psns.2013.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity of pattern transient VEP components: Contribution from M and P pathways.

Abstract: The purpose of this study was to compare contrast sensitivity estimated from transient visual evoked potentials (VEPs) elicited by achromatic pattern-reversal and pattern-onset/offset modes. The stimuli were 2-cpd, achromatic horizontal gratings presented either as a 1 Hz pattern reversal or a 300 ms onset/700 ms offset stimulus. Contrast thresholds were estimated by linear regression to amplitudes of VEP components vs. the logarithm of the stimulus contrasts, and these regressions were extrapolated to the zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Notably, confounding of various parameters occurs by necessity in this typical experimental design. Because size (Mihaylova et al, 2015 ; Pfabigan, Sailer, & Lamm, 2015 ), contrast (Souza et al, 2013 ), as well as duration affect the amplitude and latency of visual evoked potentials, there is a built-in confound when using this design.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, confounding of various parameters occurs by necessity in this typical experimental design. Because size (Mihaylova et al, 2015 ; Pfabigan, Sailer, & Lamm, 2015 ), contrast (Souza et al, 2013 ), as well as duration affect the amplitude and latency of visual evoked potentials, there is a built-in confound when using this design.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed contrast-dependent gain change both in the latency and amplitude of early P1 component, which resembles a previous single-unit study that recorded the responses of V1 neurons in cats and found that training increased neuronal contrast gain ( Hua et al, 2010 ). P1 is a visually evoked exogenous response that reflected the encoding of sensory information in visual cortex ( Voorhis and Hillyard, 1977 ; Gonzalez et al, 1994 ; Woldorff et al, 1997 ; O’Shea et al, 2010 ; Souza et al, 2013 ). Moreover, we found there is little improvement in the latency and amplitude of P1 at the location and eye change control conditions, which is also indicative of learning specificity.…”
Section: Discussionmentioning
confidence: 99%
“…They have a high contrast sensitivity, high temporal resolution, and short impulse conduction time, whereas PC neurons with a smaller receptive field are sensitive to low temporal and high spatial frequencies. [1,8,12,35,42,[45][46][47][48][49] Therefore, MC signals (high SFs) are conveyed to V1 more rapidly than PC signals (low SFs). At high SFs, the optical properties of the eye noticeably reduce the retinal contrast, resulting in decreased amplitude and delayed latency.…”
Section: Discussionmentioning
confidence: 99%